Electron beam irradiation induced compatibilization of immiscible polyethylene/ethylene vinyl acetate (PE/EVA) blends: Mechanical properties and morphology stability. (February 2017) - Entezam, Mehdi; Aghjeh, Mir Karim Razavi; Ghaffari, Mehdi
Abstract: Gel content, mechanical properties and morphology of immiscible PE/EVA blends irradiated by high energy electron beam were studied. The results of gel content measurements showed that the capability of cross-linking of the blend samples increased with an increase of the EVA composition. Also, the gel content for most compositions of the blends displayed a positive deviation from the additive rule. The results of mechanical properties showed that the tensile strength and elongation at break of the samples increased and decreased, respectively, with irradiation dose. On the other hand, the mechanical properties of the irradiated blends also depicted a positive deviation from additive rule contrary to the un-irradiated blends. A synergistic effect observed for the mechanical properties improvement of the irradiated blends and it was attributed to the probable formation of the PE-graft-EVA copolymers at the interface of the blends during the irradiation process. A theoretical analysis revealed that irradiation induced synergistic effect was more significant for EVA-rich blends with weaker interfacial interaction as compared to PE-rich blends. The morphological analysis indicated that the blend morphology was not affected obviously, whereas it was stabilized by irradiation. Highlights: Irradiation leads to PE-g-EVA copolymers formation at the interface of the blends. The interfacial interaction of the blends is reinforced by the irradiation process. Irradiation improves synergistically the mechanical properties of PE/EVA blends. Irradiation is capable of stabilizing the morphology of immiscible PE/EVA blends. Irradiation could be considered an efficient process to compatibilize PE/EVA blends.